Branching Fractions and CP Asymmetries of B→K0*1430ρω and B→K0*1430ϕ Decays in the Family Nonuniversal Z′ Model - Ying Li; En-Lei Wang; Hong-Yan Zhang (Advances in High Energy Physics)
Within the QCD factorization framework, we investigate the branching fractions and the direct CP asymmetries of decays B→K0*1430ρω and B→K0*1430ϕ under two different scenarios in the standard model and the family nonuniversal Z′ model. We find that the annihilation terms play crucial roles in these decays and lead to the major uncertainties. For decays B-→K0*-1430ρ0ω, the new Z′ boson could change the branching fractions remarkably. However, for other decays, its contribution might be clouded by large uncertainties from annihilations. Unfortunately, neither the standard model nor the Z′ model can reproduce all experimental data simultaneously under one certain scenario. We also noted that the direct CP asymmetries of B-→K0*-1430ρ0ω could be used to identify the K0*1430 meson and search for the contribution of new Z′ boson.